Figurative Language in Video of Comedy Central Stand-Up “Losing Arguments with Your Wife After Her Brain Surgery” by Jim Gaffigan - Imam Maulana; Muthia Mubasyira (JEdu: Journal of English Education, 2021)
In our daily life, we are using language to communicate with each other. A lot of linguistic aspects in a language, one of them is called figurative language. Figurative language is a word or phrase that has an isolated meaning from its exact definition. People usually use figurative language to emphasize or modify their sentences, so their sentences don't sound like something you often hear; making their sentences more unique has a lot of advantages, just imagine everyone using the same structure, emphasis, and the same emotion in their sentences, it's very horrible. Figurative language is also often used in stand-up comedy. Stand-up comedy is simply a single performed comedy actor in front of the audience.